CHARACTERISTICS OF NORSODYNE AS PLASTINATION AGENT - A. Georgieva; J. Stoyanov; N. Tsandev; D. Sivrev (Trakia Journal of Sciences)
Background: Norsodyne is a new material for conservation and durable preservation of biological objects. The form we use is H 13212 TAE (Polynt Composites USA, Inc., Bergamo, Italy). This is an unsaturated polyester resin in styrene that is of low styrene emission. Features: resin has a specific weight 1.10 g/cm2 at 20°C. Using test method MT-CUT23V the manufacturer has established that Brookfield viscosity at 23°C is 450-650 mPa.s. The jelly starts in 14-18 minutes and reaches its peak in 27-37 minutes at 23°C too. Acording to the test results of ISO 527 (2012) tensile strength of Norsodyne is 57 MPa and flexural strength is 98 MPa (ISO 178 (2011). Conclusion: This characteristic of Norsodyne indicates that the material can be used for the preservation and long-term storage of anatomical preparations for the needs of anatomy training. However, the Norsodyne needs special storage conditions. The material should be stored in a dark place. According to the manufacturer shelf life at 23°C in the dark is six months then spontaneous rubbing begins. The manufacturer's recommendations are: Store in the shade, out of direct sunlight. Keep storage temperature below 25°C. Unseal container just before use. Shelflife will be reduced reaching higher temperature.